Metabolizable protein supply according to the nrc (2001) for dairy cows grazing elephant grass Suprimento de proteína metabolizável de acordo com o nrc (2001) para vacas leiteiras pastejando capim elefante - Tadeu Vinhas Voltolini; Flávio Augusto Portela Santos; Junio Cesar Martinez; Hugo Imaizumi; Alexandre Vaz Pires; Marco Antonio Penati (Scientia Agricola, 2008)
Tropical pastures fertilized with nitrogen may have high crude protein (CP) contents with high rumen degradability. High crude protein concentrates offered to cows grazing these pastures may increase feed costs without positive effects on their performance. The objectives of this trial were to evaluate the effects of increasing metabolizable protein (MP) supply beyond the NRC (2001) recommendations for mid lactating dairy cows grazing elephant grass pasture (Pennisetum purpureum Schum. cv. Napier) managed with high stocking rates. Three concentrates (6.3 kg DM-1 cow-1 day-1) were evaluated: control (17%CP) was adjusted in relation to MP according to the NRC (2001); the other two contained extra soybean meal, to increase the CP content to 21.2% (CP) and 25.0% (CP). Twelve multiparous Holstein cows, averaging 150 days of milk production at a rate of 19.5 kg of milk day-1, were used in a 3 × 3 latin square design, replicated four times. Forage consumption was 11,270 kg DM ha-1 with 34% of green leaves and 12% CP. Milk production, corrected to 3.5% fat, milk fat, protein, lactose and total solids contents were not affected by treatments (P > 0.05). Milk urea nitrogen and plasma urea nitrogen increased linearly (P < 0.05) as the MP supply increased. Treatments did not affect (P > 0.05) body weight gain, body condition score, grazing time, ruminating time, resting time, rectal temperature and respiratory rate. Crude protein content in the concentrate formulated according to NRC (2001) is adequate for mid lactating cows grazing tropical pastures. Pastagens tropicais fertilizadas com nitrogênio podem ter alto teor de proteína bruta (PB) com alta degradabilidade ruminal. O fornecimento de concentrado com alto teor de PB para vacas mantidas nestas pastagens pode aumentar os custos sem efeitos positivos no desempenho. Objetivou-se avaliar os efeitos do suprimento de proteína metabolizável acima das recomendações do NRC (2001) para vacas em pastejo. Quatorze piquetes de capim elefante (Pennisetum purpureum Schum. cv. Napier) com 0,2 ha cada, foram usados em sistema de pastejo rotacionado. Três concentrados (6,3 kg MS-1 vaca-1 dia-1) foram avaliados. O concentrado controle com 17% PB na MS (17% PB) foi ajustado em proteína metabolizável de acordo com o NRC (2001). Os outros dois concentrados foram formulados inclusão extra de farelo de soja para conterem 21,2 (CP) e 25% (CP) de PB na MS. Foram usadas 12 vacas holandesas multíparas com 150 dias em lactação e produção de leite de 19,5 kg dia-1, arranjadas em QL 3 × 3 com quatro replicatas. A massa de forragem disponível era de 11.270 kg MS dia-1 com 34% de folhas verdes e 12% de PB. A produção de leite, produção de leite corrigida para 3,5%, teores de gordura, proteína, lactose e sólidos totais não foram afetados (P > 0,05) pelos tratamentos. O nitrogênio uréico do leite e o nitrogênio uréico do plasma aumentaram linearmente (P < 0,05) com o aumento do suprimento de proteína metabolizável. Os tratamentos não afetaram (P > 0,05) o ganho de peso, condição corporal, tempo de pastejo, tempo de ruminação, tempo em ócio, temperatura retal e a freqüência respiratória dos animais. O teor de PB no concentrado para suprir proteína metabolizável de acordo com o NRC (2001), é adequado para vacas em terço médio de lactação, mantidas em pastagens tropicais.